Developing social-emotional concepts for learning with video games. (March 2023) - Toh, Weimin; Kirschner, David
Abstract: This qualitative study uses grounded theory to derive a set of social-emotional learning concepts from a group of subjects who demonstrated social-emotional skills in video game play. We found evidence of social-emotional learning concepts through analysing game recordings, interviews, and player reflections. The concepts, including inhibitory control, prosocial behaviours, perseverance, social awareness, self-management, relationship management, emotional regulation, and optimism, are synthesised into a social-emotional theoretical model grounded in social-emotional theories of learning. Based on the findings, we suggest how teachers and game designers can create learning opportunities using the social-emotional learning concepts in video games. Highlights: We derived a set of social-emotional learning concepts in video games. User experience approaches were used to analyse the gameplay videos. We suggest how video games can be designed to teach social-emotional skills.